2016
DOI: 10.15244/pjoes/64307
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Modeling of Soil-Water Characteristic Curve of Unsaturated Soil in Collapsing Erosion Area

Abstract: Soil erosion tends to occur with rainfall runoff, thus leading to grave soil and water loss. An increase of water content in soil caused by rain makes the loss of matrix suction and the decrease of shear strength obvious, and will promote soil erosion. The soil-water characteristic curve (SWCC) can be used to describe the relationship between the water content and the matrix suction in unsaturated soil. For this paper we studied the SWCCs of the granite residual soils in a collapsing erosion area in Jiangxi Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Phoon [10] demonstrated that a lognormal random vector is suitable to model the curve-fitting parameters of the SWCC. Liu [11] reported that the Gardner model was better than the models of van Genuchten, Fredlund and Xing for an area erosion of collapsible soil near the city of Ganzhou. Zhao [12] believed that the fitting accuracy for sandmulched land was higher for the van Genuchten than the Brooks Corey model.…”
Section: Introductionmentioning
confidence: 99%
“…Phoon [10] demonstrated that a lognormal random vector is suitable to model the curve-fitting parameters of the SWCC. Liu [11] reported that the Gardner model was better than the models of van Genuchten, Fredlund and Xing for an area erosion of collapsible soil near the city of Ganzhou. Zhao [12] believed that the fitting accuracy for sandmulched land was higher for the van Genuchten than the Brooks Corey model.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important parameter for simulating the movement of moisture and the transport of solute within the soil, and plays an important role in studying and evaluating the water-holding characteristics of soil and the solute transport in soil's moisture movement [9][10][11][12][13]. The moisture characteristic curve of soil is mainly affected by soil's texture, bulk density, especially soil's structure and many other factors [14][15][16]. At present, it is difficult to theoretically calculate the relationship between the water potential and water content of soil.…”
Section: Introductionmentioning
confidence: 99%